The Geopolitical Significance of the Bering Strait Region in the 21st Century - Raková, Alena (Univerzita Karlova, Fakulta sociálních věd, 2015)
As Arctic warms twice as fast as the rest of the world and the polar ice-cap melts, the strategic importance and geopolitical significance of the Bering Strait as the only maritime gateway between the world's fastest-developing and dynamic regions, the Asia Pacific and the Arctic region, will steadily grow. The climate change triggered the reduction of the Arctic ice-cap, which results in increased maritime traffic activity as new shipping routes are becoming more viable and mineral resources more accessible. This has a tremendous impact on the region as it opens it to economic development but at the same time it puts strain on its fragile environment. The goal of the paper is to affirm that the geopolitical significance of the Bering Strait is increasing and will increase in the near future. The work examines the causes of the Bering Strait region's rise, its characteristics, challenges and opportunities together with the assessment of major regional actors' interests and approaches towards the region. Next, paper focuses The emphasis is put especially on the role of the United States and on their attitude toward the Bering Strait region. It therefore pays attention namely on the US policy and goals in the region, and on the implications the Strait's growing global importance has for the United. S rostoucím geopolitickým významem asijsko-pacifického regionu a Arktidy, zásadním způsobem roste i význam Beringovy úžiny jako strategického geopolitického území a dopravního uzlu ve 21. století. To je zapříčiněno změnou klimatu, jež má za následek tání mořského ledu v Arktidě a její celkové oteplování, čímž danou oblast otevírá novým ekonomickým možnostem. Těmi jsou zejména rostoucí dostupnost nerostných zdrojů v Severním ledovém oceánu a zpřístupňování nových námořních tras. To vše má zásadní dopad na Beringovu úžinu, jakožto jediný koridor spojující tichomořskou a arktickou oblast. Zároveň však může mít zvýšená dopravní aktivita v oblasti a zapojení více akterů neblahý vliv na zdejší ekosystém a životy původních ...